EDUKASI UPAYA PENCEGAHAN PENYAKIT JANTUNG PADA MAJLIS TA’LIM DARUSSALAM KEC. BUKIT RAYA KOTA PEKANBARU - Redho, Ahmad; Hasrianto, Nofri; Fitri, Jufenti Ade (LPPM Institut Pendidikan Nusantara Global, 2023)
Heart disease is a condition in which the heart is disturbed. The forms of the disorder itself vary, it can be a disorder in the blood vessels of the heart, the heart valves, or the heart muscle. Heart disease can also be caused by an infection or a birth defect. Other causes are imperfect heart development, infection, or oxygen-rich blood flow to the heart that is not well supplied. To overcome the need for preventive measures is that health education and promotion related to heart disease should be given especially to adults to the elderly. given education and training in herb making with materials that are easily available so that they can be made independently. The gift of knowledge and training was given to the Jamaah Majlis Ta’lim Darussalam which is not far from the campus of the Institute of Health and Technology Al Insyirah in the township of the high hill. To find out such activities for the early stages is to provide pretests and posttests to find out how far the knowledge of Jamaah MT Darussalam seta training in absorbing the information delivered so that it can be implemented in daily life. Health advice on cardiovascular disease prevention is given to the Taklim community by pre-test and post-test methods by improving knowledge, creating a healthy environment as well as the selection and processing of foodstuffs to maintain a healthy condition of the body. The activities were carried out by the lecturer of the Institute of Health and Technology Al Insyirah Pekanbaru assisted by the students of semester IV (four) with the number of those present in the activities as much as 35 people